Governance for Sexual Bullying Prevention among Students with Special Needs in Pekanbaru Special Schools - Achmad Fauzi; Seno Andri; Muchid Albintani; Febri Yuliani (Universitas Sebelas Maret, 2025)
Students with Special Needs are a vulnerable group with a high risk of experiencing sexual bullying in educational environments. Special Schools in Pekanbaru City face challenges in preventing and handling cases of sexual bullying against students with special needs due to limitations in integrated governance systems. This study aims to analyze the implementation of anti-sexual bullying governance and design an effective networking governance model for protecting students with special needs in Special Schools throughout Pekanbaru City. A qualitative approach using the case study method was conducted across all Special Schools in Pekanbaru, involving in-depth interviews with principals, teachers, parents, and related stakeholders. Policy document analysis and school environment observations were also conducted to obtain comprehensive data. The research findings indicate that anti-sexual bullying governance in Pekanbaru Special Schools remains partial and not yet integrated among stakeholders. A networking governance model is needed that involves systematic collaboration between schools, families, education departments, child protection institutions, and communities. This model includes early detection systems, safe reporting mechanisms, victim assistance, and sustainable prevention programs. The implementation of networking governance is expected to create a safe and protective learning environment for students with special needs, while strengthening institutional capacity in preventing sexual bullying.